PREPARATION OF FUTURE TEACHERS FOR BENEVOLENCE AND VOLUNTEERISM IN TIMES OF WAR - Bilavych, Halyna; Prokopiv, Liubov (Mountain School of Ukrainian Carpaty, 2023)
The Ukrainian education system today faces extremely complex challenges, including a full-scale war that has been ongoing since 2014. Despite Russia's full-scale invasion on February 24, 2022, the Ukrainian education system continues to actively develop. The purpose of this article is to analyze certain aspects of preparing future teachers for benevolence and volunteerism in times of war. Emphasis is placed on the need to address the challenges of professional preparation in the face of modern challenges, focusing on shaping future teachers as nationally conscious patriots and citizens of Ukraine. To cultivate such individuals, it is necessary to draw upon Christian morality, as Christianity serves as a formative factor that enriches and strengthens one's spirit. Benevolence and charity are principles rooted in Christianity, qualities that have been intrinsic to Ukrainian culture throughout history, and values that should be particularly pronounced in professionals. These qualities are nurtured through students' participation in various charitable activities, diverse forms of philanthropy, and volunteer work. The results of active volunteer activities by students of Vasyl Stefanyk Precarpathian National University and Ivan-Frankivsk College of Vasyl Stefanyk Precarpathian National University lead to the conclusion that benevolence is being cultivated in them during their professional training in higher education institutions during wartime. This benevolent activity by students and teachers holds special significance in terms of support and assistance to the Armed Forces of Ukraine (AFU), working with temporarily displaced persons' children, volunteer activities at the Gifted Child University, organizing master classes and sessions aimed at comprehensive personal development. Continuous support from the teaching staff and students in various forms of charitable activities, diverse forms of philanthropy, and active participation in volunteer organizations, among other efforts, attests to the widespread charitable movement in Ukraine, with educators and students at the forefront as volunteers and benefactors.